Palladium‐Loaded Cucurbit[7]uril‐Modified Iron Oxide Nanoparticles for C−C Cross‐Coupling Reactions - Benyettou, Farah; Motte, Laurence; Traboulsi, Hassan; Mazher, Javed; Pasricha, Renu; Olsen, John‐Carl; Trabolsi, Ali; Guenin, Erwan (Chemistry : a European journal, 2018)
Cucurbit[7]uril modified iron oxide nanoparticles (CB[7]NPs) were loaded with palladium to form nano‐catalysts (Pd@CB[7]NPs) that, with microwave heating, catalysed Suzuki–Miyaura, Sonogashira, and Mizoroki–Heck cross‐coupling reactions. Reactions were run in environmentally benign 1:1 ethanol/water solvent under convenient aerobic conditions. In a preliminary screening, conversions and yields were uniformly high with turn over frequencies (TOF) ranging from 64 to 7360 h−1. The nano‐catalysts could be recovered with a magnet and reused several times (6 times for Suzuki–Miayura reaction) without loss of activity. Cucurbit[7]uril modified iron‐oxide nanoparticles (CB[7]NPs) were loaded with palladium to form nano‐catalysts (Pd@CB[7]NPs) that, with microwave heating, catalysed Suzuki–Miyaura, Sonogashira, and Mizoroki–Heck cross‐coupling reactions.